PENDIDIKAN ANTI KORUPSI BAGI ORGANISASI DPD-LETHO - Tumian Lian Daya Purba; Silvester Magnus Loogman Palit (JURNAL PENGABDIAN PAPUA, 2022)
This service is carried out under the title of applying Anti-Corruption Education Science and Technology for the LETHO Regional Leadership Council organization, which was carried out on Friday, August 28 2020. Service within the LETHO Regional Leadership Council organization which is an observer of the work of the nation's children and a distributor of aid for disadvantaged areas, the Leadership Council The LETHO area of Jayapura City also oversees a clean and just government. This activity was carried out due to a lack of understanding about Anti-Corruption Education for the LETHO Regional Leadership Council organization due to the ignorance of organizational members who are very vulnerable to corruption, especially within the LETHO Regional Leadership Council in Jayapura City so that they have a better understanding and can take lessons from corruption cases that have occurred. has occurred and can take precautions in the future so that corruption does not continue to grow and become a culture, especially in Papua. The target of this service is an organization, by taking good steps and providing a better understanding of Anti-Corruption Education for the LETHO Regional Leadership Council organization as part of the community has a significant role in prevention efforts and is expected to be an agent of change and is expected to be able to has a character that is not permissive to corruption and subversive actions. It is also hoped that anti-corruption education will be included in a book.Keywords: :  Education, Anti-Corruption, Organization, DPD-LETHO